The Role of Digital Marketing in Increasing Sales (Case Study on Small and Medium Enterprises at Kerupuk Singkong Cap Tawon) - Anggelina Liuk; Warter Agustim; R Y Susanto (International Journal of Management and Business, 2026)
This study aims to investigate the role of digital marketing in increasing sales for the cassava cracker SME "Cap Tawon" in Malang, East Java, Indonesia. The study uses a quantitative approach, analyzing data from a survey involving 20 respondents (mostly women aged 24–39). It explores the impact of several dimensions of digital marketing: transaction costs, interactive communication, incentive programs, and website design. Findings show that the SME effectively utilizes various social media platforms (Facebook, Instagram, WhatsApp Business, and TikTok) for marketing purposes. Facebook and Instagram are used to present visually appealing content, while WhatsApp Business facilitates customer communication and transactions. TikTok targets a younger demographic. The results indicate a strong positive correlation between the use of these platforms and increased sales and customer reach.The study also reveals that digital marketing enables cost-effective promotional strategies while fostering customer relationships and loyalty. The SME's use of digital marketing has led to a sales increase of up to 30% and expansion into new markets.The study concludes that digital marketing is crucial for SMEs in today’s digital landscape. It highlights the importance of creating engaging content, offering incentives, facilitating customer interaction, and maintaining an appealing online presence.